Micpointer / Muna Kameelah Sauid … [et al.] - Sauid, Muna Kameelah; Ismail, Farah Liyana; Idris, Fathin Nabilah; Mohd Hassan, Haziqah; Nirahim, Norhidayah; Ismail, Nur Izzati (Division of Research and Industry Linkages, 2017)
The MicPointer is a small handheld device combining the function of a laser pointer and a small microphone into one device. This device can be used for office meetings to highlight essential information in a presentation and at the same time you can used it as a loudspeaker during the session. The devices will be connected to the computer using a NANO USB receiver. MicPointer will have a navigation button to allow users to change to next slide and also an on/off button for the microphone. The pointer will be able to reach distant targets of 5 meters in a room and for the microphone functions, it can reach distance of up to 10 meters. This tool will be appropriate for a lecture hall, meetings room and conference room. It is thus suitable to educators, motivators and tour guides as they no longer need to use physical extensions to point out nearby plants or any historical points. This device is also flexible to be carried in which users don't have to be holding two separates item at once. Plus, with this device, it helps users to avoid the items to be misplaced or lost when you have too many things on their hand. In conclusion, this product will be another evolution of technology that will help to ease human needs.